Educational and Training Interventions Aimed at Healthcare Workers in the Detection and Management of People With Mental Health Conditions in South and South-East Asia: A Systematic Review - Koly, Kamrun Nahar; Baskin, Cleo; Khanam, Ivylata; Rao, Mala; Rasheed, Sabrina; Law, Graham R.; Sarker, Farhana; Gnani, Shamini (Frontiers in Psychiatry, 2021)
Background: To bridge significant mental health treatment gaps, it is essential that the healthcare workforce is able to detect and manage mental health conditions. We aim to synthesize evidence of effective educational and training interventions aimed at healthcare workers to increase their ability to detect and manage mental health conditions in South and South-East Asia. Methods: Systematic review of six electronic academic databases from January 2000 to August 2020 was performed. All primary research studies were eligible if conducted among healthcare workers in South and South-East Asia and reported education and training interventions to improve detection and management of mental health conditions. Quality of studies were assessed using Modified Cochrane Collaboration, ROBINS-I, and Mixed Methods Appraisal Tools and data synthesized by narrative synthesis. Results are reported according to Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. A review protocol was registered with the PROSPERO database (CRD42020203955). Findings: We included 48 of 3654 screened articles. Thirty-six reported improvements in knowledge and skills in the detection and management of mental health conditions. Training was predominantly delivered to community and primary care health workers to identify and manage common mental health disorders. Commonly used training included the World Health Organization’s mhGAP guidelines (n=9) and Cognitive Behavioural Therapy (n=8) and were successfully tailored and delivered to healthcare workers. Digitally delivered training was found to be acceptable and effective. Only one study analyzed cost effectiveness. Few targeted severe mental illnesses and upskilling mental health specialists or offered long-term follow-up or supervision. We found 21 studies were appraised as low/moderate and 19 as high/ critical risk of bias. Interpretation: In low resource country settings, upskilling and capacity building of primary care and community healthcare workers can lead to better detection and management of people with mental health disorders and help reduce the treatment gap.